A game of pursuit in the halfplane - Jačiauskas, I. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. П. Ячяускас. Одна игра преследования на полуплоскостиI. Jačiauskas. Vienas persekiojimo lošimas pusplokštumėje